Effect of Fermented Rapeseed Meal in Feeds for Growing Piglets on Bone Morphological Traits, Mechanical Properties, and Bone Metabolism - Siemowit Muszyński; Aleksandra Dajnowska; Marcin B. Arciszewski; Halyna Rudyk; Jadwiga Śliwa; Dominika Krakowiak; Małgorzata Piech; Bożena Nowakowicz-Dębek; Anna Czech (Animals, 2023)
Quality feed is essential for correct bone development and proper functioning of animals. Post-weaned piglets experience a radical change in eating behaviour that can influence their feed intake. For this reason, functional feed additives and ingredients that can be used in post-weaning feeds are needed. The objective of this study was to evaluate the effects of partially replacing wheat with rapeseed meal fermented using Bacillus subtilis strain 87Y on overall bone quality and bone metabolism in weaner piglets. From the 28th day of life, barrows were fed either a standard wheat-based diet or a diet containing 8% fermented rapeseed meal (FRSM) with or without a feed additive containing enzymes, antioxidants, probiotics, and prebiotics. The experimental period lasted 60 days, after which femur quality indices were assessed. Differences in bone length and weight were observed, but there were no changes in bone mineralization or bone mid-diaphysis morphometrical traits between treatments. FRSM inclusion reduced bone mid-diaphysis biomechanical properties, but these changes were dependent on feed-additive supplementation. Analysis of the levels of serum bone turnover markers suggests the intensification of bone resorption in FRSM-fed groups as deoxypyridinoline levels increase. The results obtained warrant further research on what the disturbances in bone mechanical properties and metabolism observed in FRSM-fed weaners means for the subsequent fattening period.